2018
DOI: 10.1007/s11095-017-2315-z
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin Nano-coating for Inhibiting Surface Crystallization of Amorphous Drugs

Abstract: Gelatin nano-coatings can be conveniently applied to amorphous drugs from solution to inhibit fast surface crystallization. Unlike strong polyelectrolyte coatings, a protective gelatin coating does not require strict pairing of opposite charges. This could make gelatin coating a versatile, pharmaceutically acceptable coating for stabilizing amorphous drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…15 More recently, 20 nm thick gelatin efficiently inhibited surface crystallization with no strict requirement of opposite charges between the drug and the stabilizing agent. 16 While these studies highlight the potential of diverse coatings to inhibit surface crystallization, surface coating studies involving polymers used as pharmaceutical excipients are limited. 5,6,13,16,17 The majority of these surface coating studies have focused on the improvement of storage stability of amorphous systems.…”
Section: Introductionmentioning
confidence: 99%
“…15 More recently, 20 nm thick gelatin efficiently inhibited surface crystallization with no strict requirement of opposite charges between the drug and the stabilizing agent. 16 While these studies highlight the potential of diverse coatings to inhibit surface crystallization, surface coating studies involving polymers used as pharmaceutical excipients are limited. 5,6,13,16,17 The majority of these surface coating studies have focused on the improvement of storage stability of amorphous systems.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the positive results of the above-mentioned techniques in preventing the crystallization of amorphous surfaces, the used materials were still lacking pharmaceutical relevance. To overcome this limitation, further studies utilized biopolymers which were deposited on amorphous surfaces by dip-coating from aqueous solutions based on electrostatic interactions, such as alginate on clofazimine [15], dextran sulfate on loratadine [16], gelatin on indomethacin and nifedipine [17], and chitosan on indomethacin [18]. The coating of amorphous materials with biopolymers not only resulted in improved physical stability but also was able to improve its powder flowability and dissolution performance [18].…”
Section: Introductionmentioning
confidence: 99%
“…Because PDDA is not a pharmaceutical polymer, Teerakapibal et al tested gelatin as a coating polymer. 6 Unlike PDDA, gelatin is a weak polyelectrolyte and not a homopolymer, having both acidic and basic amino acid segments. They found that a gelatin coating can offer similar protection against crystallization and that a gelatin coating is “forgiving” in that it does not require strict pairing of opposite charges.…”
Section: Introductionmentioning
confidence: 99%